2010
DOI: 10.17221/1519-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

How can wheat landraces contribute to present breeding?

Abstract: Two sets of winter wheat landraces and obsolete cultivars were studied in three-year field experiments, and compared with 3 modern control cultivars. The higher spike productivity in modern cultivars could mainly be attributed to an increased number of grains in a spikelet and harvest index (HI), whereas thousand grain weight (TGW) has only a slight effect. Landraces and old cultivars proved to have a higher content of crude protein. Spike productivity characteristics, except for TGW, showed a negative correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 5 publications
4
23
0
Order By: Relevance
“…Our results show a boost of durum wheat yield in Mediterranean countries resulting from the use of improved varieties, in agreement with previous studies (Koç et al 2000;De Vita et al 2007;Royo et al 2008). This yield increase was accompanied by a significant decrease in grain protein content, agreeing with Dotlačil et al (2010). The known negative relationship between yield and protein content (Rharrabti et al 2001) is associated with dilution of nitrogen compounds when carbohydrate deposition increases through photosynthesis (Lawlor 2002;Martre et al 2003).…”
Section: Discussionsupporting
confidence: 74%
“…Our results show a boost of durum wheat yield in Mediterranean countries resulting from the use of improved varieties, in agreement with previous studies (Koç et al 2000;De Vita et al 2007;Royo et al 2008). This yield increase was accompanied by a significant decrease in grain protein content, agreeing with Dotlačil et al (2010). The known negative relationship between yield and protein content (Rharrabti et al 2001) is associated with dilution of nitrogen compounds when carbohydrate deposition increases through photosynthesis (Lawlor 2002;Martre et al 2003).…”
Section: Discussionsupporting
confidence: 74%
“…A previous study with the same historical series used here reported an average yield gain of 0.61% year -1 (Royo et al 2008), which indicates that the yield increases achieved during the 20th Century largely compensated for the decreases in the protein content of the newly released cultivars. Several studies have reported increases in grain yield accompanied by significant decreases in grain protein content (Motzo et al 2004;De Vita et al 2007;Dotla cil et al 2010;Nazco et al 2012). The negative relationship between yield and protein content (Rharrabti et al 2001) has been associated with a dilution effect of nitrogen compounds when carbohydrate deposition increases through photosynthesis (Lawlor 2002;Martre et al 2003).…”
Section: Genetic Gains In Grain Quality Traitsmentioning
confidence: 99%
“…According to our previous observations, the frequency of the discovery of a novel HMW-GS in hexaploid wheat (Triticum aestivum L.) is very low, especially within the modern cultivars. Nevertheless, the screening of the collections of the maintained landraces and obsolete cultivars could increase the probability of finding novel or very lowly expressed HMW-GSs, even using such a simple analytical approach as SDS-PAGE (Gregová et al 2004) and landraces can contribute also breeding programes at present (Dotlačil et al 2010). The nucleotide sequence of the gene 1Dy12.3 and the deduced amino acid sequence of the protein were deposited in the GenBank database (GenBank: EF472958, Gregová & Mihálik 2007, unpublished).…”
Section: Glutenin Extraction and Hmw-gs Analysismentioning
confidence: 99%